Al-Dakhīl in Language (Rules of Grammar, Sentences, and Qira'ah) - Nabila Fasya; Lailatul Karimah; Zahrotul Umamah Zheero; Islamiyah M (Tilawah: Journal of Al-Qur'an Studies, 2026)
The study of al-dakhil in Arabic is an important aspect in understanding the forms of changes or additions of certain elements in sentence structure, both in grammar and in the study of Quranic recitation. The phenomenon of al-dakhil often gives rise to variations in form and meaning, necessitating research that can explain the concept more comprehensively. The research problem formulation covers the definition and scope of al-dakhil according to grammar rules, its impact on sentence structure and meaning, and its application in several narrations of recitation that indicate additional elements or changes in reading form. This study aims to outline the linguistic basis behind the emergence of al-dakhil, explain its function in Arabic sentence construction, and analyze examples of its application in recitations that have varying readings. This research employed a qualitative method based on literature review, examining classical nahwu literature, modern linguistic works, and qirā’ah books. The results show that al-dakhil not only functions as an additional element in a sentence but can also influence syntactic structure and interpretation of meaning. In the qirā’ah study, al-dakhil was found to be one of the factors causing differences in reading forms between Qur’ans, particularly in aspects of the ziyādah letter, changes in vowels, and certain morphological patterns. These findings confirm that the concept of al-dakhil plays a crucial role in understanding the dynamics of Arabic and the diversity of Qur’anic qirā’ah.